The proof of sufficient descent condition for a new type of conjugate gradient methods - Mustafa, Mamat; Abashar, A; Rivaie, M; Mohd, I; Omer, O (2013)
Conjugate gradient methods are effective in solving linear equations and solving non-linear optimization. In this work we compare our new conjugate gradient coefficient E k with classical formula under strong Wolfe line search; our method contains sufficient descent condition. Numerical results have shown that the new E k performs better than classical formula.